Monoclonal gammopathy and visceral leishmaniasis - Ferreira, J.; Centurión, M.É.; Armoa, A.; Zarza, J. (Anales del Sistema Sanitario de Navarra, 2013)
Monoclonal gammopathies (MG) are mainly associated with plasma cell dyscrasias and less frequently to rheumatological, autoimmune and infectious diseases.Its association with visceral leishmaniasis (VL) is exceptional. VL should be included in the differential diagnosis of MG in endemic and non endemic areas.